Visual Attention-Related Processing: Perspectives from Ageing, Cognitive Decline and Dementia - Tales, Andrea; Hanley, Claire (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Visual attention is essential for environmental interactions, but our ability to respond to stimuli gradually declines across the lifespan, and such deficits are even more pronounced in various states of cognitive impairment. Examining the integrity of related components, from elements of attention capture to executive control, will improve our understanding of related declines by helping to explain behavioural and neural effects, which will ultimately contribute towards our knowledge of the extent of dysfunctional attention processes and their impact upon everyday life. Accordingly, this Special Issue represents a body of literature that fundamentally advances insights into visual attention processing, featuring studies spanning healthy ageing, mild cognitive impairment, and dementia